Animal identification - Donovan, John; Brown, Patricia (Current protocols in immunology, 2006)
Proper identification of animals is crucial in research, whether the animals are being used as experimental subjects, for breeding purposes, or as a source for tissues, cells, or fluids. This unit provides specific protocols for the ear punch (notch) and ear tag methods for mouse, rat and hamster; tattoos for mouse, rat and rabbit; and the correct use of a subcutaneous transponder system for all of the above species.